Community-based tourism product development based on the community identity of Klong-Lad-Ma-Yom floating market Bangkok, Thailand - Phukamchanoad, Phusit (Turyzm/Tourism, 2022)
This article aims to develop products for community-based tourism in order to increase the value of those based on the authentic identity of the Klong-Lad-Ma-Yom floating market. The research results showed that, in 2004, there was the beginning of a fresh coconut juice ice cream business in the Klong-Lad-Ma-Yom floating market. At that time, stories and folktales related to the product were created which helped the local people promote it as a part of community-based tourism; this effort contributed to its fundamental economic development. After the successive waves of the COVID-19 pandemic had subsided, many tourists still came to buy a variety of ready-to-eat food and desserts. Food prices were negotiable and free trials were available. In other words, the Klong-Lad-Ma-Yom floating market was a “negotiable market”, where each local stall had its own designs and businesses run together peacefully. A community-based product could effectively add value to the Klong-Lad-Ma-Yom floating market in a sustainable manner.